2010
DOI: 10.1093/nar/gkq869
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas Genome Database: improved comparative analysis and population genomics capability for Pseudomonas genomes

Abstract: Pseudomonas is a metabolically-diverse genus of bacteria known for its flexibility and leading free living to pathogenic lifestyles in a wide range of hosts. The Pseudomonas Genome Database (http://www.pseudomonas.com) integrates completely-sequenced Pseudomonas genome sequences and their annotations with genome-scale, high-precision computational predictions and manually curated annotation updates. The latest release implements an ability to view sequence polymorphisms in P. aeruginosa PAO1 versus other refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
686
1
13

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(706 citation statements)
references
References 41 publications
6
686
1
13
Order By: Relevance
“…We also sequenced the genome of the ancestral PAO1 wild-type strain for comparison. Genomes were assembled using the published PAO1 genome sequence as a reference (Stover et al, 2000;Winsor et al, 2011). In all, our analysis showed the HC harbored only three mutations when compared with the wild-type ancestor, including lasR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also sequenced the genome of the ancestral PAO1 wild-type strain for comparison. Genomes were assembled using the published PAO1 genome sequence as a reference (Stover et al, 2000;Winsor et al, 2011). In all, our analysis showed the HC harbored only three mutations when compared with the wild-type ancestor, including lasR.…”
Section: Resultsmentioning
confidence: 99%
“…The mutations were single-nucleotide polymorphisms in lasR (PA1430) and in PA2408, as well as an 18 base-pair truncation in psdR (PA4499). PA2408 encodes a probable adenosine triphosphate (ATP)-binding component of an ABC (ATP-binding cassette) transporter, and psdR encodes a transcriptional regulator (Kiely et al, 2008;Winsor et al, 2011) (Table 2). Targeted Sanger sequencing of all three loci in two additional HC and cheater isolates from day 12 of two independent in vitro evolution experiments revealed that mutations in lasR and psdR are ubiquitous in isolates displaying both phenotypes, but mutations in PA2408 are not (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The libraries were sequenced using the Illumina MiSeq V2 platform with a paired-end protocol and read lengths of 150 nt. The sequence reads were mapped onto the P. aeruginosa PAO1 reference genome, which is available for download from the Pseudomonas Genome Database (http://www.pseudomonas.com) 46 , using the 'RNA-Seq and expression analysis' application of the CLC genomics Workbench 6.0 (CLC Bio, Aarhus, Denmark). The following criteria were used to filter the unique sequence reads: maximum number of hits for a read of 1, minimum length fraction of 0.9, minimum similarity fraction of 0.8 and maximum number of two mismatches.…”
Section: Methodsmentioning
confidence: 99%
“…While choline is ubiquitous in eukaryotes, the ability to synthesize choline or GB de novo from phosphatidylethanolamine or glycine is less prevalent in bacteria and evidence suggests that it is absent in the pseudomonads (42). While de novo choline synthesis has not been demonstrated in the pseudomonads, transporters for exogenous choline import are ubiquitous within this group based on analyses of current genome sequences (43). Import of choline and GB has been well studied in these and other bacteria, and I direct readers to relevant reviews on the topic (44)(45)(46).…”
Section: Choline and Gb Import Versus De Novo Synthesismentioning
confidence: 99%